The processing of humour by individuals suffering from schizophrenia - Varga, Eszter; Herold, Róbert; Schnell, Zsuzsanna; Horváth, Réka; Simon, Mária; Hajnal, András; Tényi, Tamás (European journal of humour research, 2016)
Humour is an important component of social cognition. The last few years of cognitive research of schizophrenia provided a considerable amount of empirical evidence about social cognitive impairments in this serious neurodevelopmental disorder. The aim of this study is to investigate verbal humour comprehension and its cognitive background in a group of schizophrenic patients with normal intelligence. Results showed that patients were practically unable to understand verbal jokes, Gricean implicatures, and second-order Theory of Mind (ToM) tasks, when compared with healthy subjects. As the statistical analysis shows, verbal joke comprehension of patients living with schizophrenia significantly correlated with the comprehension of the linguistic incongruity of the Gricean implicatures and with verbal intelligence. On the other hand, smooth handling of verbal jokes did not significantly depend on the comprehension of second-order ToM and did not correlate with the comprehension of the intended meaning of the speaker’s utterance in the Gricean implicatures’ tasks.